When you sing it now, just like new : First Nations poetics, voices, and representations - Ridington, Robin (University of Nebraska Press, 2006)
A collection of essays examining the issues surrounding the listening, recording, and sharing of First Nations voices, stories, and songs. These essays, which contextualize stories within anthropology, flow from Robin Ridington and Jillian Ridington's decades of work with the Athapaskan-speaking Dane-zaa people, who live in Peace River area.